Adult Learning in a Migration Society. - Hoggan, Chad, 1971-; Hoggan-Kloubert, Tetyana, 1981- ([Place of publication not identified] : Routledge, 2021)
Migration is an old, perhaps perpetual, phenomenon. Currently, it is an urgent challenge involving huge numbers of people who leave their home in search of a better life. Differences in language, customs, and norms are often joined by specific manifestations of xenophobia born of particular differences between host countries and their current influx of migrants. In a pronounced way, then, migration reveals important societal questionsof solidarity, of identity, of transition and transformation, of human rights and obligations. The explorations in this collection highlight individual stories of migrants, showcase innovative research methods, and explore concepts and theories that might be usefully applied toward learning needs in a migration society. Including insights from scholars across 14 different countries, this book offers an international perspective on the role of adult education in addressing migration. Such international comparisons hold great potential for seeing new possibilities in any single country, whether in Europe, North America, or across the world.
Keywords: Immigrants -- Education; Immigrants -- Education -- Case studies; Adult education; Adult education -- Case studies; EDUCATION / General